Fatty acid influence on Prochilodus lineatus (Characiformes, Prochilodontidae) embryo cryopreservation parameters. - Costa, Raphael da Silva [UNESP]; Souza, Fabrício Marçal Silva [UNESP]; Senhorini, José Augusto; Bashiyo-Silva, Cristiane [UNESP]; Verissímo-Silveira, Rosicleire [UNESP]; Coelho, Geovanna Carla Zacheo [UNESP]; Siqueira-Silva, Diógenes Henrique; Ribeiro, Cristiele da Silva [UNESP]; Ninhaus-Silveira, Alexandre [UNESP] (Wiley, 2018)
This study aimed to evaluate the vitellogenic transference and incorporation of long-chain polyunsaturated fatty acids (LC-PUFA) into the membranes of Prochilodus lineatus embryos, aiming to increase the permeability to cryoprotectants and resistance to electric fields. One hundred thirty broodstock of P. lineatus were fed with control (C) or fish oil-supplemented diets (FO) for 12 months. The fatty acid (FA) profle was determined using gas chromatography. For the neutral fraction, the FO group had a decrease in monounsaturated fatty acids (MUFA) and an increase in n3PUFA and, n6PUFA. To test for cryoprotectant toxicity, embryos were exposed for 20 min to a cryoprotectant solution of 1,2-Propanediol (Prop) at a concentration of 5 or 6 molar (M). For FO, a reduction in survival of 33.1% was observed in 5 M, and no survival was observed at 6 M. Embryo samples were exposed the six polarized electric fields (3.4–51.6 joules), and with 11.2 J of energy, the control group exhibited reduced survival in 98.3% of the fish, whereas the FO presented superior resistance, exhibiting a survival similar to that of the OJ up to 40.2 J. We conclude that FA were transferred between P. lineatus broodstock to the embryos, with an increase in LC-PUFA resulting in lower survival rates in the cryoprotectant test in the FO group and a greater physical plasticity of FO embryos to electrical field tests.
Keywords: biotechnology; cryoprotectants; electric field; fatty acids composition; Prochilodus lineatus; toxicity